Playful and mathematical language as a permanent practice in the classroom - Bohórquez Rubiano, Genny Rocío; Trujillo Alarcón, Sandra; Mojica Ojeda, Adriana María (Rastros Rostros, 2023)
Language is expressed through multiple and varied forms, such as gestures, mimicry, traffic signaling systems, musical rhythms, among others. For the human species, oral language is produced from articulated sounds that allow it to interpret and signify its world and that of others. Professor Luis Baena affirms "Man perceives the world through cognitive processes of sensitivity, imagination where he has the ability to interpret and create meanings about himself and about the realization"; and it is precisely with language that he communicates these processes.